IONIC SPECIATION IN A DYSTROPHIC RED LATOSOL UNDER COFFEE CROP AND HIGH DOSES OF GYPSUM - Ramos, Barbara Zini; de Lima, Jose Maria; Serafim, Milson Evaldo; Coscione, Aline Renee; Ferraz, Raul Magalhaes; Amorim, Lucas Mota; Lopes, Guilherme (Coffee Science - ISSN 1984-3909, 2019)
The cultivation of coffe crops in Brazil, especially on Latosols, has been increasing over the years, despite limitations such as aluminum toxicity, low fertility and very long drought periods. In this scenario, soil amendments to mitigate these restraints are necessary. Since these limitations are not restricted to the arable layer, application of gypsum becomes an efficient alternative to sustain soil fertility and deepen the root system to get water from the deeper layers of soil. However, high doses of gypsum can cause unbalance among Ca2+, Mg2+ and K+. The objective of this work was to evaluate these bases as well as their ionic pairs, and the presence of sulfate along the soil profile 16 months after the application of high gypsum doses in a Latosol under coffee crops. An inicial dose of gypsum was applied in the entire area, followed by four treatments, in triplicate and randomized blocks, set as follows: G0 - zero gypsum applied over the planting line after the initial soil preparation; G7- 7 t ha-1 of gypsum in the planting line (1.75 kg m-1); G56 - 56 t ha-1 of gypsum in the planting line (14 kg m-1), all with brachiaria between the coffee planting lines; and CV7 - 7 t ha-1 of gypsum in the line and no brachiaria between the planting lines. The soil profile was sampled in layers up to 2.40 m depth and the soil solution was extracted by suctioning the sample-saturated paste. Following this extraction, the soil solution was analyzed by combustion for total carbon contents, ion chromatography and ICP-OES/flame photometry, for chemical species, and speciation was done using Minteq software. After 16 months of gypsum application, 96% of K+ in soil solution was at 0.35 to 0.45 m in its free form. Leaching of Ca2+ and Mg2+ occurred predominantly in their free forms, although a more significant contribution of CaSO4 0 and MgSO4 0 ionic pairs was observed when compared to K2SO40.